DONOR SELECTION: IMMUNOGENETICS AND HISTOCOMPATIBILITY - Torres, Margareth Afonso; Rampim, Gisele Fabianne; Cardoso, Juliana Fernandes; Vergueiro, Carmem; Pereira, Noemi Farah; Lima, Alberto Cardoso Martins (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION